Human and social impact of tecnological changes in Pakistan: A report on a survey conducted by the University of Dacca and published with the assistance of UNESCO - Husain , A. F. A. (Pakistan Oxford University Press, 1956)
The present Report embodies the results of a research on the social and economic effects of technological change in Pakistan which was undertaken by a group of young scholars at this University under the leadership of Professor A.F.A. Husain of the Department of Commerce during the academic session 1953-4. The survey was planned by Professor Husain in collaboration with Dr. A. Farouk, Lecturer in Commerce, and Mr. A.N.M. Muniruzzaman, Lecturer in Statistics. These three persons were also responsible for the direction of the field-work which was carried out mainly by twelve teachers and forty stu dents of the University, including the Government College of Commerce, Chittagong. These teachers and students belonged mainly to the Departments of Economics, Commerce, Statistics, Political Science and International Relations. The names of these workers are given in Appendix A of the Report. Mr. K. Fazlur Rahman, Lecturer in Commerce, assisted considerably in the tabulation and analysis of field-data. All the tables have, how ever, been thoroughly checked by Professor Husain. The Report has been written by Professor Husain who has also edited the case studies, having conducted a majority of the case interviews himself. He has been assisted by Dr. Farouk and Mr. Rahman in writing the Chapter on Methods and by Mr. A.H.M. Nooruzza man, Lecturer in Political Science in writing certain sections of the Chapter on Social Conditions. The two excellent maps of East Bengal given in the Report have been drawn by Mr. Momtaz Ali, draughtsman in the Department of Geography, under the supervision of the Head of the Department of Geography.
Volume 1. Reports of case-studies.